PENERAPAN MODEL PEMBELAJARAN CONNECTING, ORGANIZING, REFLECTING, AND EXTENTING DENGAN MEDIA POSTER TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK - Salsabila, Nafisa (Jurnal Edukasi dan Penelitian Matematika, 2023)
This research was inspired by the lack of students’ mathematical communication ability. Mathematical communication ability is one of the basic abilities that need to be achieved in mathematics. In fact, learning activities in SMK N 9 Batam are not optimal in facilitating students to improve these aspects. The average score of the mathematical communication ability test that does not meet the value of mathematical communication ability criteria is evidence of this. This research uses the Connecting, Organizing, Reflecting, and Extending learning model that comes with poster media to improve mathematical communication ability. This study has the purpose to describe the development of students’ mathematical communication ability as long as the CORE learning model comes with poster media is applied and comparing the mathematical communication ability of students who learn using the CORE learning model comes with poster media with students who learn by direct learning model. This research is descriptive and quasi-experimental research using research design is the non-equivalent control group design. After analyzing the data, through quizzes the mathematical communication skills of the experimental class had increased, then through the final test the mathematical communication ability of students who studied using the CORE learning model that comes with poster media was better than students who studied with direct learning models in class XI SMK Negeri 9 Batam. Keywords– Mathematical Communication Ability, Connecting, Organizing, Reflecting, and Extending learning model, Poster